Two-port network model of fixed-speed wind turbine generator for distribution system load flow analysis - Rudy Gianto; Kho Hie Khwee; Hendro Priyatman; Managam Rajagukguk (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2019)
Load flow analysis has always been used in determining the steady-state operation of an electric power or distribution system. For conventional power system without wind turbine generator, the method for load flow analysis has been well established. However, for modern system embedded with wind turbine generator, the investigation of analysis method is still an active research area. This paper proposed a new method to integrate fixed-speed wind turbine generator into distribution system load flow analysis. The proposed method is derived based on two-port network theory where the parameters of induction generator of the wind turbine generator are embedded in general constants of the two-port network. The proposed method has been tested and verified using a representative electric distribution system.